The role of ROTEM variables based on clot elasticity and platelet component in predicting bleeding risk in thrombocytopenic critically ill neonates. (27th October 2020) - Parastatidou, Stavroula; Sokou, Rozeta; Tsantes, Andreas G; Konstantinidi, Aikaterini; Lampridou, Maria; Ioakeimidis, Georgios; Panagiotounakou, Polytimi; Kyriakou, Elias; Kokoris, Styliani; Gialeraki, Argyri; Douramani, Panagiota; Iacovidou, Nicoletta; et al.
Abstract: Background: Our aim was to investigate the role of thromboelastometry (ROTEM) parameters, including maximum clot elasticity (MCE) and platelet component (PLTEM MCE and PLTEM MCF), in early prediction of bleeding events in thrombocytopenic critically ill neonates. Material and methods: This single‐center, prospective cohort study included 110 consecutive thrombocytopenic neonates with sepsis, suspected sepsis, or hypoxia. On the first day of disease onset, ROTEM EXTEM and FIBTEM assays were performed and the neonatal bleeding assessment tool was used for the evaluation of bleeding events. Results: Most EXTEM and FIBTEM ROTEM parameters significantly differed between neonates with (n = 77) and without bleeding events (n = 33). Neonates with bleeding events had significantly lower PLTEM MCE and PLTEM MCF values compared to those without bleeding events ( P  < .001). Platelet count was found to be strongly positively correlated with EXTEM A5 (Spearman's rho = 0.61, P  < .001) and A10 (rho = 0.64, P  < .001). EXTEM A10 demonstrated the best prognostic performance (AUC = 0.853) with an optimal cutoff value (≤37 mm) (sensitivity = 91%, specificity = 76%) for prediction of bleeding events in thrombocytopenic neonates. Conclusions: EXTEM A5 and EXTEM A10 were found to be strong predictors of hemorrhage, compared to most ROTEM variables quantifying clot elasticity and platelet component in thrombocytopenic critically ill neonates.